2022
DOI: 10.1371/journal.pone.0274545
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 surveillance by RT-qPCR-based pool testing of saliva swabs (lollipop method) at primary and special schools—A pilot study on feasibility and acceptability

Abstract: Background Since the onset of the COVID-19 pandemic, children have been mentally and physically burdened, particularly due to school closures, with an associated loss of learning. Therefore, efficient testing strategies with high sensitivity are necessary to keep schools open. Apart from individual rapid antigen testing, various methods have been investigated, such as PCR-based pool-testing of nasopharyngeal swabs, gargle, or saliva samples. To date, previous validation studies have found the PCR-based saliva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
0
0
2
Order By: Relevance
“…Overall, our research suggests better acceptance of saliva-based PCR testing compared to nasal swab antigen testing among parents of children across all three age groups. This is in line with prior studies that also reported a high acceptance of PCR saliva-based testing in children ( 19 , 39 , 61 , 62 ). Similarly, combined throat and nasal swabs have also been described as a feasible alternative down to 4 years of age in Western Australia ( 63 ).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our research suggests better acceptance of saliva-based PCR testing compared to nasal swab antigen testing among parents of children across all three age groups. This is in line with prior studies that also reported a high acceptance of PCR saliva-based testing in children ( 19 , 39 , 61 , 62 ). Similarly, combined throat and nasal swabs have also been described as a feasible alternative down to 4 years of age in Western Australia ( 63 ).…”
Section: Discussionsupporting
confidence: 92%
“…Obwohl in Deutschland verschiedene Projekte mit PCR-Pool-Testverfahren implementiert wurden, fanden diese zu unterschiedlichen Zeitpunkten mit unterschiedlich vorherrschenden Virusvarianten statt: Nordrhein-Westfalen [18], Mecklenburg-Vorpommern [19] und Bayern [21,27]. Daher sind diese Projekte eingeschränkt vergleichbar: Testzeiträume und -prozeduren sowie Verordnungen und Hygienemaßnahmen unterschieden sich.…”
Section: Zeitperiodeunclassified
“…in Deutschland im Mai 2021 PCR-Pooltestungen mittels "Lolli-Methode" flächendeckend an Grund-und Förderschulen ein [18]. Diese Tests galten als ungefährlich, einfach durchführbar und von Kindern besser akzeptiert als Nasen-oder Rachenabstriche [19]. Pooltestungen wurden als ressourceneffizient und bei niedriger Prävalenz als gut skalierbar bewertet [20].…”
Section: Introductionunclassified